IDENTIFIKASI DESA WISATA TEMATIK DALAM RANGKA MENDUKUNG DESTINASI WISATA SUPER PREMIUM LABUAN BAJO NUSA TENGGARA TIMUR - Sari Bandaso Tandilino (Jurusan Pariwisata Politeknik Negeri Kupang, 2022)
NTT's tourism development is carried out with reference to the second mission of the 2018-2023 RPJMD, namely to build NTT as one of the gateways and centers for national tourism development with the tagline Ring of Beauty so that the tourism sector has been designated as a prime mover for development supported by 1,305 destinations and 273 tourist villages. Labuan Bajo is the only super premium tourist destination as well as a super priority as well as the location for the G20 Summit in 2022. The number of tourist visits to NTT in 2019 was 1,113,212 people with foreign exchange reaching IDR 2,226,422,000,000 or the equivalent of 42% when compared to the posture The 2019 NTT APBD was IDR 5.3 trillion, but the Covid-19 pandemic caused a contraction of a decrease of 90% in 2020 which occurred not only because of PPKM, but also the inability of tourism village managers to implement tourism villages based on their absolute and comparative advantages . The NTT province has a total of 3,026 villages spread across 22 districts and as many as 330 as tourist villages or only 11% so that the Labuan Bajo Flores Authority Executing Agency (BPOLBF) has established 30 thematic tourism villages spread across 10 districts in NTT namely Flores Island, Lembata Island and Alor Island and 1 district in NTB namely Sumbawa Island which is abbreviated as FLORATAMA or Flores, Alor, Lembata and Bima. The formulation of the problem is how to identify thematic tourist villages in order to support the super premium tourist destination of Labuan Bajo, NTT. This type of quantitative research uses survey and experimental research methods with a combination of quantitative and qualitative data analysis techniques. The purpose of this study was to identify thematic tourist villages in 30 locations using data collection techniques through site visits as well as FGDs to 140 managers of thematic tourist villages as respondents and process them using qualitative data analysis techniques in the form of presentation in the form of matrices, graphs, and charts. 43% identified culture-based thematic tourism villages. and 7% nature-based and 28% ecotourism. and 11% had the theme of agro-tourism while 12% had the theme of ancient sites and MICE tourism.